2011
DOI: 10.1590/s1516-35982011001100038
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of metabolizable energy utilization for maintenance and gain and evaluation of Small Ruminant Nutrition System model in Santa Ines sheep

Abstract: -This study was carried out to estimate efficiencies of the utilization of metabolizable energy for maintenance (k m ) and weight gain (k g ) and to evaluate the Small Ruminant Nutrition System (SRNS) model in predicting dry matter intake and average daily gain of growing Santa Ines sheep. Twenty-four non-castrated Santa Ines sheep, at 50 days of age and with average body weight of 13.00 ± 0.56 kg, respectively, were used. After a 10-day adaptation period, four animals were slaughtered to be used as reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
2
12
1
3
Order By: Relevance
“…As the lambs aged, their serum levels of total protein decreased linearly, probably due to increased protein demand for muscle tissue deposition, which, during the lamb's initial life phase, is on the rise (Resende, Silva, Lima, & Teixeira, 2008;Regadas Filho et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the lambs aged, their serum levels of total protein decreased linearly, probably due to increased protein demand for muscle tissue deposition, which, during the lamb's initial life phase, is on the rise (Resende, Silva, Lima, & Teixeira, 2008;Regadas Filho et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm the values described by Gonzaga Neto et al (2005), who also reported an increase of 0.66 to 0.68 km as the concentrate was increased in the Morada Nova lamb diet. Regadas Filho et al (2011) and Oliveira et al (2014) observed an increase from 0.68 to 0.73 km and 0.59 to 0.71 km, respectively, as the energy was incremented in the Santa Ines sheep diet. The metabolizable energy efficiency for weight gain was directly related to gain composition (GARRETT, 1980).…”
Section: Figure 1 Exponential Relationship Between Heat Production (mentioning
confidence: 87%
“…Protein deposition is energetically less efficient than fat synthesis because the synthesis and degradation (turnover) of body protein reduces the energy efficiency of its accumulation (GARRETT, 1980;GEAY, 1984;OWENS et al, 1995). However, fat deposition at high levels, as observed in early animals, may reduce the overall efficiency of utilization of metabolizable energy for weight gain due to the high energy required to maintain the same body mass as in late animals (REGADAS FILHO et al, 2011). High fat deposition is a biological need for animals adapted to regions with seasonality, as this necessitates the storage of fat as an energy reserve source, which may explain the reduced efficiency of utilization of metabolizable energy for weight gain.…”
Section: Figure 1 Exponential Relationship Between Heat Production (mentioning
confidence: 99%
See 2 more Smart Citations